Episodic and prospective memory difficulties in 13-year-old children born very preterm. (7th March 2023) - Stedall, Paulina M.; Spencer-Smith, Megan M.; Lah, Suncica; Doyle, Lex W.; Spittle, Alicia J.; Burnett, Alice C.; Anderson, Peter J.
Abstract: Objectives: Children born very preterm (VP) are susceptible to a range of cognitive impairments, yet the effects of VP birth on long-term, episodic, and prospective memory remains unclear. This study examined episodic and prospective memory functioning in children born VP compared with their term-born counterparts at 13 years. Method: VP ( n = 81: born <30 weeks' gestation) and term ( n = 26) groups were aged between 12 and 14 years. Children completed: (i) standardized verbal and visuospatial episodic memory tests; and (ii) an experimental time- and event-based prospective memory test that included short-term (within assessment session) and long-term (up to 1-week post-session) tasks. Parents completed a questionnaire assessing memory functions in everyday life. Results: The VP group performed worse on all measures of verbal and visuospatial episodic memory than the term group. While there were no group differences in event-based or long-term prospective memory, the VP group performed worse on time-based and short-term prospective memory tasks than term-born counterparts. Parents of children born VP reported more everyday memory difficulties than parents of children born at term, with parent-ratings indicating significantly elevated rates of everyday memory challenges in children born VP. Conclusions: Children born VP warrant long-term surveillance, as challenges associated with VP birth include memory difficulties at 13 years. This study highlights the need for greater research and clinical attention into childhood functional memory outcomes.